Analysis of structure and function relationships of an autoantigenic peptide of insulin bound to H-2K(d) that stimulates CD8 T cells in insulin-dependent diabetes mellitus - Wong, F. Susan (National Academy of Sciences, 2002)
The recognition of MHC–peptide complexes by T cells is governed by structural considerations that are determined by the sequences of the individual components and their interaction with each other. We have studied the function of a highly diabetogenic CD8 T cell clone that is specific for insulin B15-23:H-2K(d). We have then related this to modeled MHC–peptide structures. The native peptide binds poorly to H-2K(d), because of the small glycine residue at peptide position p9 that is incapable of productive interactions with the hydrophobic residues of pocket F. In addition, electrostatic repulsions between the peptide glutamate residue at position 7 and 152D of the MHC molecule heavy chain contribute to the poor binding. However, B chain peptide 15-23 bound to K(d) shows excellent T cell stimulation and the induction of CD8 cytotoxic T cells. Peptide substitution has also shown that p6G is likely to be a T cell antigen receptor interaction site. Our studies have shown that the predictions seen in the models correlate closely with the observed effects in functional assays and provide insight into how this peptide, which would not be predicted to stimulate these cells on H-2K(d) binding studies alone, could activate such highly pathogenic T cells.